Desenvolvimento de uma metodologia para análise de ressarcimentos de aparelhos de som, associados aos distúrbios na rede elétrica da CEMIG, testando dispositivos mitigadores - Borges, Jonmil Marques (2012)
Nowadays, researches and developments related to Power Quality subject have motivated a great afford of work in many centers involved with studies on electrical engineering. Amongst the areas of interest, emerge the investigations associated to the operation of large, medium and small electric-electronic devices. These are frequently found in industrial, commercial and residential installations. Added to the questions of performance analysis of these products, the degree of equipment sensitivity, supportability and withstand capabilities are becoming major concerns in this context. These worries are quite relevant so as to define the equipment/process dependence with the supply conditions as well as the definition of compensation solutions such as consumers refunding. Recognizing, therefore, the importance of these facts, this work is devoted to obtaining the allowable limits of voltage and current of a stereo. A proposed methodology and structure for laboratory destructive testing is presented involving tests at power frequency, simulation of falling out of the high voltage in the low voltage cables and impulsive transients that guided the development of the of thermal and dielectric withstand capability curves of the equipment under investigation. Based on the results obtained, some real cases of compensation claims along with an electric utility are presented and simulated in computer application APR. In addition, further studies are carried out to evaluate the influence of mitigating devices in analysis techniques and their impact on emission of reports for electrical damages claim.